BEYOND TECHNOCRATIC DIGITALIZATION: INTEGRATING SCIENTIFIC AND CRITICAL PARADIGMS IN DIGITAL EDUCATION MANAGEMENT - Mad Umar Mad Umar; Nuryati Nuryati; Abdul Muin; Matlaul Anwar; Risqon Nujuludin (Universitas Islam Negeri Mataram, 2026)
Digital transformation has profoundly reshaped the governance and management of education systems through the expansion of data-driven decision-making, learning analytics, and platform-based management. However, research on digital education management remains largely dominated by a scientific–technocratic paradigm that prioritises efficiency, performance measurement, and system optimisation. While this orientation can strengthen organisational accountability, it often underplays the social, ethical, and political dimensions embedded in digital governance practices. This study addresses this limitation by examining digital education management through an integration of scientific and critical paradigms. Using a qualitative integrative literature review, we analysed peer-reviewed publications (2020–2025) retrieved from Scopus, Web of Science, and Google Scholar. The analysis followed a three-stage procedure comprising paradigmatic mapping, thematic coding, and conceptual integration. The findings indicate a persistent fragmentation between technocratic and critical approaches, alongside limited attempts at substantive integration. Building on this synthesis, the study proposes an integrative conceptual framework that conceptualises digital education management as both a technical practice and a social praxis. The study contributes theoretically by bridging competing paradigms in educational management scholarship and practically by offering a reflective foundation for digital education governance that is efficient, participatory, and socially just.